The Gendered Nose and its Lack: “Medieval” Nose-Cutting and its Modern Manifestations - Patricia Skinner (Journal of Women's History, 2014)
This article explores the historical background to modern instances of nose-cutting and nose-slitting as 'traditional' punishments, particularly targeted against women. Using examples drawn from the medieval period, it is argued that the practice, whilst often threatened, occurred relatively rarely, and was often in fact used as a means of criticising the uncontrolled abuse of power by rulers. When it was used as a punitive measure, it required specific justification. The practice itself is documented in the Old Testament of the Bible, and it is this common source that appears to have inspired later usage.